OPTICAL PROPERTIES OF ZNO NANOCOMPOSITE DOPED WITH POLYMER POLYETHYLENE GLYCOL: REVIEW - Jarad, Amar N.; Abdulelah, Haider; Dheyab, Raed A. (Antis-Publisher, 2026)
Objective: The integration of inorganic nanostructures into polymer matrices has revolutionized the field of functional materials, enabling the creation of composites with tailored properties for advanced applications, with PEG/ZnO nanocomposites emerging as a subject of intense research interest due to their synergistic functionalities. Method: This review provides a comprehensive analysis of PEG/ZnO nanocomposites, meticulously detailing the various synthesis strategies, including in-situ growth, ex-situ blending, and sol-gel methods, and discussing how these methods influence the morphology and dispersion of ZnO within the PEG matrix. Result: The review delves into the profound modifications in the composite's structural, optical, thermal, electrical, and mechanical properties as characterized by techniques such as XRD, FTIR, Raman spectroscopy, UV-Vis, PL, DSC, and SEM/TEM, while also mapping the vast application spectrum spanning biomedical fields, energy storage, photocatalysis, and ultraviolet shielding. Novelty: Finally, the review addresses the current challenges and future perspectives, outlining the path for next-generation PEG/ZnO-based materials, thus offering valuable insights into the advancement of functional nanocomposites.